Understanding the burden of menstrual health issues in a health university setting: a study from Kerala - Swapna, K. G.; Rajamohanan, K.; Namitha, P.; Jisharaj, V. R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Menstruation affects women, often leading to several health issues that impact academic and work performance. Menstrual health receives limited attention in institutional settings, despite its prevalence. Objective: To estimate the burden of menstrual health problems. Methods: A cross-sectional online survey was conducted among female staff, students and faculty members of Kerala University of Health Sciences (KUHS). A structured, self-administered online-questionnaire assessed the burden of menstrual health problems. Quantitative data were expressed as mean (SD) or median (IQR), qualitative data as frequency and percentage. The outcome variables were dichotomised as problems present or absent. Results: The prevalence of menstrual health problems was 96.4% (95% CI 95.6 to 96.8%). More than half of them reported that menstrual bleeding impacted their daily activities and 39.7% were prevented from going to their institution. However, only 15.2% reported that they would take menstrual leave if it were implemented as a policy. About 31.6% of participants reported a change in menstrual pattern after COVID-19 infection. The overall prevalence of premenstrual symptoms (PMS) was 77.2%, with mild PMS 37.3%, moderate PMS 30% and severe PMS 9.9%. Conclusions: Menstrual health problems are common and significantly affect women’s academic and professional life. Gender-sensitive institutional measures are essential to support women's health and productivity.